A modified presurgical orthopedic (nasoalveolar molding) device in the treatment of unilateral cleft lip and palate - Subramanian, Chitravelu Siva; Prasad, N. K. K. Koteswara; Chitharanjan, Arun B.; Liou, Eric Jein Wein (European Journal of Dentistry, 2016)
Nasoalveolar molding (NAM) can be done effectively to reshape the nasal cartilage and mold the maxillary dentoalveolar arch before surgical cleft lip repair and primary rhinoplasty. Presurgical NAM helps as an adjunct procedure to enhance the esthetic and functional outcome of the surgical procedures. We have developed a modified NAM device to suit to the needs of the patients coming from distant places for the treatment. This device helps in reducing the number of frequent visits the patient needs to take to the craniofacial center. The purpose of this presentation is to report this treatment technique and discuss its application.
Keywords: Infant orthopedics; presurgical infant orthopedics presurgical nasoalveolar molding; unilateral cleft lip and palate